Efficacy of Pyrotinib in HER2-Overexpressing Salivary Duct Carcinoma With Lung Metastasis: A Case Report - Yang, Zi-yan; Huang, Jia-huan; Chen, Bo; Xu, Chun-wei; Lei, Lei; Wang, Xiao-jia; Fang, Mei-yu (Frontiers in Oncology, 2020)
Salivary duct carcinoma（SDC）is an aggressive salivary gland tumors（SGC）, which is diagnosed at an advanced stage. And it becomes a big challenge to the systemic therapy stay away from the recurrent or metastatic due to its rarity and heterogeneity. People with human epidermal growth factor receptor-2 (HER2) overexpression can be observed in some of SDC, so that we evaluated the targeted therapy is available for metastatic disease. Here we present a 62-year-old male patient with HER2-positive SDC presented with complaints of pain and progressive swelling in anterior neck area. A needle biopsy of the lymph node in the neck confirmed that it was a SDC with metastases to lymph node. After completion of treated with six cycles of TFP chemotherapy, pulmonary metastases recurring after half a year. Patient received re-chemotherapy but does not respond wel. He took Pyrotinib, a pan-ErbB receptor tyrosine kinase inhibitor (TKI), as a third-line treatment, showed pulmonary metastatic lesions completely disappeared after after three months of treatment. Patient is still alive and continues to receive pyrotinib targeted therapy.